Effects of spectral composition of artificial light on the colonization patterns of mobile epibenthic macrofauna in marinas - Pablo Saenz-Arias; Sofía Ruiz-Velasco; Carlos Tapia; José Manuel Guerra-García; Macarena Ros; Ignacio Gestoso; Carlos Navarro-Barranco (Marine Pollution Bulletin, 2026)

Global patterns and regional insights into kelp forest protection, restoration, and stewardship - Aaron M. Eger; Adriana Verges; Akshata MehtaFalkland Islands; Albert Pessarrodona; Alejandra Mora-Soto; Alejandro Bernal-Ibáñez; Aleksandra Smorygo; Alexandria M. Niese; Alexis Savard-Drouin; Andrew Kalani Carlson; Ang Put; Annalisa Falace; et al. (Journal of Applied Phycology, 2026)
Kelp forests are among the most extensive and productive coastal ecosystems, yet they remain underrepresented in global conservation policy despite widespread declines driven by interacting global- (i.e., ocean warming, marine heatwaves) to local-scale stressors. At the same time, kelp conservation and restoration efforts are expanding rapidly across regions, but measures of success and syntheses tend to primarily focus on ecological conditions and trends, not on conservation and restoration actions. To fill this gap, we developed a comparative global dataset of kelp conservation initiatives based on expert-derived regional narratives from 209 participants spanning 35 regions with kelp forests. We applied a structured presence–absence scoring framework across six domains: conservation actions, restoration approaches, governance actors, conservation objectives, social dimensions, and funding structures, supplemented by regional expert knowledge to enable cross-regional comparison. Across regions, conservation was characterised by strong emphasis on monitoring (86% of regions), multi-actor governance (scientific institutions 94%, government agencies 86%), and protecting existing forests (66%), while active restoration was undertaken in half of the regions. Social engagement (66%) and links to fisheries and livelihoods (69%) were widespread, whereas explicit climate adaptation objectives were less common (17%). We identify a set of conservation profiles that describe how kelp forest conservation is advancing in different ecological and governance contexts worldwide. These findings highlight that scaling kelp conservation is as dependent on the social, financial, institutional, and policy systems that govern implementation, as it is on ecological knowledge and technical capacity. By bridging regional knowledge with global analysis, this study provides a framework for aligning locally grounded conservation action with global biodiversity targets.

Concomitant effects of algae invasion and sea urchin mass mortality drive the shift from barrens to turf grounds - Alejandro Bernal-Ibáñez; Jordi Boada; Eva Cacabelos; Marta Florido-Capilla; Raül Triay-Portella; Patrício Ramalhosa; Rodrigo P. Silva; João Canning-Clode; Ignacio Gestoso (Marine Environmental Research, 2026)

Entangled ecosystems: the impact of macroplastic litter on Mytilus galloprovincialis communities in northwestern Spain - Jacob Houvener; Ignacio Moreu; Eva Cacabelos; Ignacio Gestoso; Jose M. F. Babarro; Mark Lenz (Frontiers in Marine Science, 2025)
Plastic litter in the ocean has gained significant attention over recent decades, with much of the focus on microplastics. However, macroplastic litter is prevalent in marine environments, and while its effects on single organisms is well documented, its effects on community-level biological structures remain poorly understood. This study investigates the impact of macroplastic litter—specifically polyethylene film (shopping bags) and nylon filament (fishing line)—on Mytilus galloprovincialis aggregates and their associated fauna in the Ría de Vigo, NW Spain. Using a fully factorial experimental design, 30-mussel aggregates were assembled incorporating plastic litter in different abundances and were deployed in situ for 4 weeks. After this time, physiological responses (respiration and filtration), structural complexity (rugosity index), particulate matter retention, body condition index (BCI), and associated mobile faunal diversity were measured. Mussels in the High/Filament treatment showed an 18% lower respiration rate and a 65% reduction in filtration capacity compared to controls, while the Low/Filament treatment reduced filtration by 40%. No significant effects were found on BCI, particulate retention as well as on the diversity and composition of the associated macrofauna. Interestingly, aggregates with low plastic content exhibited a slightly higher structural complexity than those with high amounts of plastic. This study highlights that macroplastics can subtly alter the functionality of mussel beds without dramatically affecting the diversity of the associated fauna. These insights underscore the need to assess physical interactions of organisms with plastic litter also at the community level.

The spread of Aoroides longimerus Ren & Zheng, 1996 across the Mediterranean and the Atlantic: genetic diversity, anthropogenic transport, and ecological implications - JOSÉ MANUEL GUERRA-GARCÍA; ANDREA DESIDERATO; SERENA MUCCIOLO; CARLOS NAVARRO-BARRANCO; MACARENA ROS; JASMINE FERRARIO; PAULA MORETTI; AGNESE MARCHINI; NAWFEL MOSBAHI; SOFÍA RUIZ-VELASCO; IGNACIO GESTOSO; PATRÍCIO RAMALHOSA; et al. (Mediterranean Marine Science, 2025)
Accurate knowledge of the global distribution of non-indigenous species (NIS) is essential for understanding their invasion dynamics and for implementing timely management measures. This study reports the first records of the marine amphipod Aoroides longimerus, putatively native to the East Asian coast, in Italy (2018), Spain (2019) and Tunisia (2022) and provides the earliest documented record of the species in its introduced European range (Portugal, 2011). Furthermore, it expands the species’ known distribution in mainland Portugal (including the northernmost record), Macaronesia (with first records in the Canary Islands and Madeira), and confirms its presence along the Atlantic coasts of France and the Netherlands. Aquaculture facilities, particularly those associated with oyster farming, are probably the primary vector of introduction, while recreational boating may have contributed significantly to secondary dispersal. In comparison to other exotic amphipods, A. longimerus remains absent from many marinas, ports and/or aquaculture facilities in the Mediterranean Sea and adjacent regions, such as the Red Sea. This suggests that the species may still be in the early stages of expansion, or that its dispersal ability across marinas and ports is more limited than that of other amphipods. The present study, however, highlights several key ecological traits of A. longimerus: (i) it can survive year-round despite seasonal fluctuations, and reach high local densities, (ii) it exhibits strong colonisation capacity, as shown by its rapid establishment on settlement plates, and (iii) it displays opportunistic feeding behaviour, primarily consuming detritus. These characteristics underscore the importance of continuous surveillance and effective communication with stakeholders to prevent further expansion of this species.

The role of marine debris as a vector, dispersal agent, and substrate for non-indigenous species on Oceanic Islands (Northeast Atlantic) - Patrício Ramalhosa; João G. Monteiro; Sabine Rech; Ignacio Gestoso; Soledad Álvarez; Francesca Gizzi; Paola Parretti; Nuno Castro; Silvia Almeida; Jesús Lopez Jiménez; Macarena Ros; Cláudio Cardoso; et al. (Marine Pollution Bulletin, 2025)

Biodiversity on the move: Epibiotic communities associated with pelagic sargassum in the northeast Atlantic - João Faria; Laura Piazzese; Patrício Ramalhosa; Antoine Eberling; Miguel Devesa; Clara Benadon; Rodrigo Silva; Ignacio Gestoso; João Monteiro; Manuela Parente; Gustavo M. Martins; João Canning-Clode; et al. (Marine Environmental Research, 2025)

High contribution of an invasive macroalgae species to beach wrack CO2 emissions - Iván Franco Rodil; Valle Perez Rodriguez; Alejandro Bernal-Ibáñez; Mauro Pardiello; Federica Soccio; Ignacio Gestoso (Journal of Environmental Management, 2024)

Management of non-indigenous species in Macaronesia: Misconceptions and alerts to decision-makers - Nuno Castro; Pedro M. Félix; Ignacio Gestoso; José L. Costa; João Canning-Clode (Marine Pollution Bulletin, 2024)

Editorial: New plastic pollution types and novel sources of microplastic pollution in marine systems - Sonja M. Ehlers; Julius A. Ellrich; Ignacio Gestoso (Frontiers in Marine Science, 2024)

Exploring visual methods for monitoring marine non-indigenous species colonizing artificial structures in the Madeira archipelago (NE Atlantic) - Soledad Álvarez; Ignacio Gestoso; Patrício Ramalhosa; João Canning-Clode (Regional Studies in Marine Science, 2024)

New species and new records of bryozoan species from fouling communities in the Madeira Archipelago (NE Atlantic) - Javier Souto; Patrício Ramalhosa; Jasmine Ferrario; Lydia Png-Gonzalez; Soledad Álvarez; Ignacio Gestoso; Natacha Nogueira; João Canning-Clode (Marine Biodiversity, 2023)
Hull fouling is considered to be the most significant vector of introduction of marine non-indigenous species (NIS) in the Madeira Archipelago (NE Atlantic) because these islands provide a vital passage route for many ships. The transfer of species between boat hulls and artificial substrates in marinas is known to be high. Bryozoans are among the most common groups of marine invertebrates growing on this type of substrate. In recent years, significant advances have been made in our knowledge about the biodiversity of bryozoans in the Madeira Archipelago. Nonetheless, the currently recognized numbers remain far from reflecting the actual bryozoan species richness. In this context, we examine bryozoan samples stemming from NIS monitoring surveys on artificial substrates along the southern coast of the Madeira Archipelago, in four recreational marinas and in two offshore aquaculture farms. This has yielded new information about ten bryozoan species. Two of them, Crisia noronhai sp. nov. and Amathia maderensis sp. nov., are described for the first time, although at least the first one was previously recorded from Madeira but misidentified. Bugula ingens , Cradoscrupocellaria insularis , Scruparia ambigua , and Celleporaria brunnea are recorded for the first time in Madeira. Moreover, the material of C. brunnea was compared with the type, and a biometric analysis was performed with material from the Atlantic and Mediterranean. All samples identified as C. brunnea in both regions are the same species, and the variations described in the literature apparently reflect high intracolonial variability. Finally, we provide new information for the descriptions of 4 additional bryozoans, namely, Crisia sp. aff . elongata , Cradoscrupocellaria bertholletii , Scrupocaberea maderensis , and Tricellaria inopinata .

Testing differences of marine non-indigenous species diversity across Macaronesia using a standardised approach - Nuno Castro; Ignacio Gestoso; Patrício Ramalhosa; Evandro Lopes; Corrine Almeida; Ana Costa; Manuela Parente; Eva Cacabelos; Rogélio Herrera; José L. Costa; João Canning-Clode (Marine Pollution Bulletin, 2023)

Location and building material determine fouling assemblages within marinas: A case study in Madeira Island (NE Atlantic, Portugal) - Juan Sempere-Valverde; Patrício Ramalhosa; Sahar Chebaane; Free Espinosa; João Gama Monteiro; Alejandro Bernal-Ibáñez; Eva Cacabelos; Ignacio Gestoso; José Manuel Guerra-García; João Canning-Clode (Marine Pollution Bulletin, 2023)

Monitoring Non-Indigenous Species with Passive Sampling Methods in an Oceanic Island - Anna Diem; Patrício Ramalhosa; Eva Cacabelos; Jasmine Ferrario; Nuno Castro; Filipe Henriques; João Gama Monteiro; Paula Chainho; Christopher Kim Pham; João Canning-Clode; José Paula; Ignacio Gestoso (Journal of Marine Science and Engineering, 2023)
The synergistic effects of biological invasions have long been considered significant causes of biodiversity loss worldwide. Therefore, early detection monitoring is crucial in mitigating nonindigenous species (NIS) threats. In the marine environment, settlement plates were used as monitoring devices in ports, but this method was mainly applied to assess the sessile benthic community and is less efficient in collecting the mobile biota and accessing its diversity. Moreover, as the potential expansion of NIS to the surrounding coastal environment is still poorly understood, a pilot study was conducted focusing on two aspects: (i) improving the feasibility of the settling method under different environmental contexts and (ii) enhancing the capacity of the developed prototypes to collect more representative samples (i.e., sessile and mobile biota). Three different prototypes were designed: a box prototype consisting of PVC plates encapsulated by a plastic bottle, a CD prototype with CDs surrounded by a net, and a PVC prototype with uncovered PVC plates. The prototypes were deployed inside a marina and in an outside area on Madeira Island, Portugal. Results indicate that the PVC prototype was the most efficient regarding monitoring the sessile community, whereas the box prototype showed the highest abundance of the mobile fauna. The location influenced both the sessile community composition and the number of mobile taxa. Our findings suggest combining features from prototypes to encompass the whole benthic community better.

Role of non-indigenous species in structuring benthic communities after fragmentation events: an experimental approach - Eva Cacabelos; Ignacio Gestoso; Patrício Ramalhosa; João Canning-Clode (Biological Invasions, 2022)

Non-Indigenous Species on Artificial Coastal Environments: Experimental Comparison between Aquaculture Farms and Recreational Marinas - Lydia Png-Gonzalez; Patrício Ramalhosa; Ignacio Gestoso; Soledad Álvarez; Natacha Nogueira (Journal of Marine Science and Engineering, 2021)
Globally, there is growing concern regarding the effects of the increasing anthropogenic pressures in marine communities. Artificial structures such as marinas and aquaculture facilities serve as invasion hotspots; hence, monitoring fouling communities on these structures can be valuable for detecting new invasions. In the current study, 24 settlement PVC plates were deployed for three months to compare the recruitment ability of these two artificial environments along the south coast of the offshore island of Madeira (NE Atlantic). The results showed higher variations in the species richness between regions (SW vs. SE) than between artificial habitats (sea-cages vs. marinas), although the community composition differed. Cnidaria and Bryozoa were the most representative groups in the aquaculture systems, while Bryozoa and Chordata were in the marinas. A sum of 18 NIS was recorded for the study, accounting for between 21.88% and 54.84% of the total number of species in the aquaculture facilities and marinas, respectively. The higher NIS percentage from the marinas was even more explicit in the SE coast, where Cradoscrupocellaria bertholletii, Parasmittina alba, and Botrylloides niger distinctly dominated fouling populations. The results suggest that at least some particular NIS previously reported in the studied marinas successfully colonized sea-cages. Future assessments need to address the potential role of aquaculture facilities as drivers for the secondary spread of NIS. Additionally, two new records are considered for Madeira: Eudendrium capillare and Ericthonius punctatus.

The collapse of marine forests: drastic reduction in populations of the family Sargassaceae in Madeira Island (NE Atlantic) - Alejandro Bernal-Ibáñez; Ignacio Gestoso; Peter Wirtz; Manfred Kaufmann; Ester A. Serrão; João Canning-Clode; Eva Cacabelos (Regional Environmental Change, 2021)
Species of the genera Cystoseira , Ericaria , Gongolaria , and Sargassum (family Sargassaceae) are key components of the Mediterranean-Atlantic marine forests, essential for biodiversity and ecosystem functioning. Populations of these foundational species are particularly vulnerable to anthropogenic impacts, likely to be intensified under future scenarios of climate change. The decline and even disappearance of these species have been reported in different areas of the world. At Madeira Island (NE Atlantic), populations of Gongolaria abies-marina , Ericaria selaginoides , Sargassum vulgare , and Sargassum filipendula , the most ecologically relevant species in Macaronesian marine forests, have been suffering a drastic decline during the last decades, especially on the southern coast of the island, where anthropogenic pressure is higher than on the north coast. The lack of sufficient temporal coverage on qualitative and quantitative studies of Sargassaceae communities in Madeira poses a challenge to establish a specific period for this decline. Consulting qualitative studies and historical records, we have set for the first time a timeline that shows an evident decrease in Sargassaceae populations in the last 20 years on Madeira Island. Following this timeline, we pinpoint the start of this decline in the first decade of the 2000s. This can be particularly confirmed for places like Funchal and Reis Magos, with significantly higher historical records. Currently, most benthic communities on shallow subtidal rocky reefs along the south coast are dominated by sea urchins and crustose coralline algae, the so-called sea urchin barrens. However, in some cases, they are entirely covered by a layer of sediment. We discuss the possible factors contributing to these drastic changes, bringing Madeira’s marine forests to a dramatic decline. As many animal species rely on marine forests, the decline of Sargassaceae populations represents an invaluable ecological loss for the coastal ecosystem of the island.

The Role of Sea-Urchins in Marine Forests From Azores, Webbnesia, and Cabo Verde: Human Pressures, Climate-Change Effects and Restoration Opportunities - Alejandro Bernal-Ibáñez; Eva Cacabelos; Ricardo Melo; Ignacio Gestoso (Frontiers in Marine Science, 2021)
Marine forests ecosystems are typical of temperate rocky benthic areas. These systems are formed by canopy-forming macroalgae (Laminariales, Tilopteridales, and Fucales) of high ecological value that provide numerous ecosystem services. These key species are also indicators of good environmental status. In recent decades, marine forests have been threatened by different impacts of local and global origin, putting their stability and survival in question. On a global scale, in many temperate areas of the planet, marine forests have been replaced by “sea-urchins barrens.” We present a general overview of sea-urchins’ population status in the archipelagos of Azores, Webbnesia (Madeira, Selvagens, and Canary Islands) and Cabo Verde, focusing on their role in the maintenance of the so-called “alternate stable state.” After an in-depth evaluation of the different anthropogenic and environmental pressures, we conclude that sea-urchins population explosion has been facilitated in the benthic habitats of Madeira and Canary Islands, preventing the recovery of canopy-forming macroalgae assemblages and being one of the main drivers in maintaining a stable barren state. Diadema africanum is the main barrens-forming species in Webbnesia, where it reaches high densities and strongly impacts macroalgal assemblages. On the other hand, in the most pristine areas, such as the Selvagens Islands and other Marine Protected Areas from the Canary Islands, the density of D. africanum is up to 65% lower than in the nearby Madeira Island, and macroalgal communities are preserved in good status. This information is critical for marine environmental management, highlighting the urgent need for implementation of appropriate control mechanisms and restoration actions headed to the conservation of marine forests in Macaronesian archipelagos.

Disease Outbreak in a Keystone Grazer Population Brings Hope to the Recovery of Macroalgal Forests in a Barren Dominated Island - Francesca Gizzi; João Gama Monteiro; Rodrigo Silva; Susanne Schäfer; Nuno Castro; Silvia Almeida; Sahar Chebaane; Alejandro Bernal-Ibáñez; Filipe Henriques; Ignacio Gestoso; João Canning-Clode (Frontiers in Marine Science, 2021)
Macroalgal forests play a key role in shallow temperate rocky reefs worldwide, supporting communities with high productivity and providing several ecosystem services. Sea urchin grazing has been increasingly influencing spatial and temporal variation in algae distributions and it has become the main cause for the loss of these habitats in many coastal areas, causing a phase shift from macroalgae habitats to barren grounds. The low productive barrens often establish as alternative stable states and only a major reduction in sea urchin density can trigger the recovery of macroalgal forests. The present study aims to assess if the 2018 disease outbreak, responsible for a strong reduction in the sea urchin Diadema africanum densities in Madeira Island, was able to trigger a reverse shift from barren grounds into macroalgae-dominated state. By assessing the diversity and abundance of benthic sessile organisms, macroinvertebrates and fishes before, during and after that particular mass mortality event, we evaluate changes in benthic assemblages and relate them to variations in grazer and herbivore densities. Our results revealed a clear shift from barren state to a macroalgae habitat, with barrens characterized by bare substrate, sessile invertebrate and Crustose Coralline Algae (CCA) disappearing after the mortality event. Overall variations in benthic assemblages was best explained by four taxa (among grazers and herbivores species). However, it was the 2018 demise of D. africanum and its density reduction that most contributed to the reverse shift from a long stable barren state to a richer benthic assemblage with higher abundance of macroalgae. Despite this recent increase in macroalgae dominated habitats, their stability and persistence in Madeira Island is fragile, since it was triggered by an unpredictable disease outbreak and depends on how D. africanum populations will recover. With no control mechanisms, local urchin populations can easily reach the tipping point needed to promote a new shift into barren states. New conservation measures and active restoration are likely required to maintain and promote the local stability of macroalgal forests.

A Comprehensive First Baseline for Marine Litter Characterization in the Madeira Archipelago (NE Atlantic) - Soledad Álvarez; Ignacio Gestoso; Alicia Herrera; Léa Riera; João Canning-Clode (Water, Air, & Soil Pollution, 2020)

Intertidal assemblages across boulders and rocky platforms: a multi-scaled approach in a subtropical island - Eva Cacabelos; Ignacio Gestoso; Patrício Ramalhosa; Léa Riera; Ana I. Neto; João Canning-Clode (Marine Biodiversity, 2019)

Local benthic assemblages in shallow rocky reefs find refuge in a marine protected area at Madeira Island - Filipe Alves; João Canning-Clode; Cláudia Ribeiro; Ignacio Gestoso; Manfred Kaufmann (Journal of Coastal Conservation, 2019)

Biofilms shaping compositions of macrofouling assemblages: An initial barrier against NIS settlement? - Eva Cacabelos; Patrício Ramalhosa; João Canning-Clode; Jesus Troncoso; Celia Olabarria; Cristina Delgado; Sergey Dobretsov; Ignacio Gestoso (Frontiers in Marine Science, 2019)

A new methodology for the study of biological invasions on coastal communities - Ignacio Gestoso; Patrício Ramalhosa; Eva Cacabelos; Jasmine Ferrario; Nuno Castro; João Monteiro; Paula Chainho; Christopher Pham; João Castro; João Canning-Clode (Frontiers in Marine Science, 2019)

Susceptibility of two co-existing mytilid species to simulated predation under projected climate change conditions - Jose M. F. Babarro; María José Abad; Ignacio Gestoso; Elsa Silva; Celia Olabarria (Hydrobiologia, 2018)

Interactive effects of predation and facilitation during the settlement process of non-indigenous species - Gestoso Ignacio; Ramalhosa Patricio; Ferreira Lurdes; Canning-Clode João (Frontiers in Marine Science, 2016)

Selection of habitat by a marine amphipod - Ignacio Gestoso; Celia Olabarria; Jesús S. Troncoso (Marine Ecology, 2014)
Marine algae are known to provide habitats for a wide range of marine organisms. Populations of marine epiphytal invertebrates are generalists and are less adapted to live in only one macroalga species. However, there are some examples of local adaptation and, in particular, amphipods have shown strong host specificity. Amphitholina cuniculus , an amphipod with an alga‐burrowing habit, has been mainly observed in B ifurcaria bifurcata mats on the intertidal rocky shores of the southern region of the Galician coast ( NW Spain; 42º11.27′ N, 8º48.25′ W). We designed a laboratory experiment conducted in June 2009 to analyse the association between the amphipod and the macroalga. In particular, we hypothesised that (i) this species would exhibit different behaviour during the day and at night, and (ii) adults of A . cuniculus would prefer B . bifurcata as habitat rather than F ucus vesiculosus or S argassum muticum . Results supported the hypothesis that adults of A. cuniculus preferred B . bifurcata , although such preferences did not show the day/night variability predicted. This amphipod might be considered a specialist species, at least on rocky intertidal shores along the Galician coast.